A case study on Microfinance in Kuching city: customers' awareness and acceptance towards Amanah Ikhtiar Malaysia (AIM) Micro Finance programs / Ramsis William Agim - William Agim, Ramsis (2011)
Poverty is a still a problem in the Malaysian economy. Despite of the numerous government efforts in eliminating poverty, the problem continues to persist. In order to meet the poverty crisis, the government of Malaysia reformed the economic policy and undertook a small-scale credit programs. Microfinance is one of the objectives of New Economic Policy (NEP) which was launched by the Malaysian Government to reduce poverty and income disparities in Malaysia. At present, the programs have progressed and could be evaluated for its success towards the aim of reducing poverty. In 1999 it was reported that 8.5% of the population was under the poverty line. However, after only five years, i.e., in 2004, Malaysia managed to reduce the population living below the poverty level to only 5.7%. The present study attempts to evaluate the awareness and acceptance of Amanah Ikthiar Malaysia micro credit program in Kuching city. This study focuses on the differences in means between participants of AIMs’ micro finance programs and participants of other micro finance programs (i.e. Tekun and Mara). The result shows that there was a significant difference in means of awareness, benefits, perception and satisfaction between participants of AIM's micro finance programs and participants of other micro finance programs. Based on the findings of the study, it is recommended that AIM should conduct more campaign and promotional activities especially in Kuching. Hopefully the recommendations will boost up AIM’s awareness and acceptance in this area and other areas nearby therefore to be a more favorable micro finance provider in the future.